Stanley E. Porter, Καταλλάσσω in Ancien Greek Literatur, with Reference to the Pauline Writings, Córdoba, Estudios de Filología Neotestamentaria, nº 5, Ediciones El almendro, 1994, 189 pp. ISBN 84-8005-011-X (Minerva, 2019)
Review: Stanley E. Porter, Καταλλάσσω in Ancien Greek Literatur, with Reference to the Pauline Writings, Córdoba, Estudios de Filología Neotestamentaria, nº 5, Ediciones El almendro, 1994, 189 pp. ISBN 84-8005-011-X